Hydrogeological and hydrochemical characteristics of alluvial aquifers in the Brahmaputra Valley, Assam, India - Patgiri, A. D.; Devi, Swapna (Journal of Nepal Geological Society, 2000)
The Brahmaputra Valley comprising a thick pile of unconsolidated alluvial deposits encompasses an area of about 63,450 km2 in the state of Assam, India. It is composed of unclassified Older and Newer alluvial deposits consisting of boulders, cobbles, pebbles, gravels as well as sand of various grades, silt, and clay. The area is occupied predominantly by Recent and Older floodplains represented by udifluvents (younger alluvial soils), and palenstalfs and haplaquents (older alluvial soils). The Piedmont zone fringing the northern foothill region of the valley is represented by usthorthents (Bhabar Soils) and haplaquolls (Terai Soils). Hydrogeologically, the northern and southern banks of the river Brahmaputra differ considerably. The northern bank is generally characterised by a single aquifer system of great thickness and varied composition down to a depth of about 150 m, where mostly an unconfined aquifer is found. Semiconfined aquifers are also seen at places where the sediment s are stratified. Shallow tube wells yield 30 to 60 ml/hr for a drawdown of 1- 2 m. The yield of deep tube wells is found to range from I00 to 250 ml/hr for a drawdown of 4- 10 m. The depth to water table in the piedmont zone varies from 5 to 40 m with an average fluctuation of 3-10 m. The average hydraulic conductivity of the aquifer system is found to range from 30 to 200 m/day. The southern bank is characterised by the presence of unconfined and semiconfined aquifers. Some perfectly confined aquifers as well as some perched aquifers are also encountered locally. Shallow tube wells can yield 25- 35 ml/hr for a drawdown of 2 m while deep tube wells are capable of yielding 100-250 ml/hr for a drawdown of 4-8 m. The water table rests within a depth of 2-6 m from the land surface. The average hydraulic conductivity varies from 30 to 200 m/day. The decadal variation of water table in the alluvial aquifer of the Brahmaputra Valley indicates a rising trend of water level. Dynamic groundwater potential of the shallow aquifer zone is within the range of 15,440 mcm. Hydrochemically, the groundwater of the Brahmaputra Valley is found to be suitable for domestic and irrigation purposes, except for higher concentration of iron. The pH value ranges from 6.8 to8.7, indicating neutral to slightly alkaline nature of groundwater. Low value of electrical conductivity and total dissolved solids implies fresh nature of groundwater. Piper trilinear plot reveals the preponderance of alkaline earths (Ca, Mg) and weak acids (HCO3 + CO3) over alkalis (Na, K) and strong acids (SO4, Cl) in the groundwater of the majority of the study area indicating Ca + Mg- HCO3 type.